The role of anionic lipids in enterococcus faecalis physiology - Chen, Qingyan (Nanyang Technological University, 2020)
Enterococcus faecalis is a Gram-positive, facultative anaerobic, diplococcal, opportunistic pathogen, causing many nosocomial infections. Virulence factor secretion and assembly occurs at spatially restricted foci at the septum of the cell in E. faecalis. The foci coordinating these processes occur at the cell division plane, which is coincident with anionic lipid domains. The anionic lipids phosphatidylglycerol (PG) and cardiolipin (CL) are the major phospholipids (PLs) in Gram-positive bacterial membranes. Here, to determine the role of anionic PLs in E. faecalis physiology, we constructed a pgsA inducible mutant and cls deletion mutants to investigate the roles of PG and CL in the localization of secretion and virulence factor assembly machinery, as well as to antimicrobial resistance. We observed that pgsA is essential for cell viability in E. faecalis, but cls1 and cls2 are not. As expected for an essential gene, depletion of pgsA and its gene product, which is required for PG biosynthesis, resulted in severe cell morphology defects and cell death. Protein expression of the sortases involved in focal virulence factor assembly were all decreased in the pgsAind at low anhydrotetracycline (ATc) concentrations (when PG is presumed to be depleted) and cls2-deficient mutants. However, delocalization of the sortases was only observed in the PG-depletion mutant, but not in cls-deficient mutants, suggesting independent roles for these two anionic PLs in virulence factor assembly. Furthermore, cls2-deficiency resulted in increased EbpC production on a single cell level, whereas neither the piliation on a population level nor the localization of EbpC was altered. In addition, in pgsAind at low ATc concentrations, the cell wall was less cross-linked and cell surface deposition was altered, which may serve as a compensatory reaction to PG depletion. Finally, we demonstrated that pgsAind at low ATc concentrations became more sensitive to cell membrane targeting antimicrobials but more resistant to cell wall targeting antimicrobials, and Cls2 contributed to daptomycin (DAP) sensitivity, suggesting that PG and CL differently contribute to antimicrobial resistance in E. faecalis. In summary, both PG and CL contribute to virulence factor assembly and antimicrobials resistance, but in different ways. These findings pave the way for future studies on the roles of phospholipids in E. faecalis biology and virulence, and may shed light on the development of new antimicrobials and treatment strategies.